Pollen Developmental Arrest: Maintaining Pollen Fertility in a World With a Changing Climate - Pacini, Ettore; Dolferus, Rudy (Frontiers in Plant Science, 2019)
During evolution of land plants, the haploid gametophytic stage has been strongly reduced in size and the diploid sporophytic phase has become the dominant growth form. Both male and female gametophytes are parasitic to the sporophyte and reside in separate parts of the flower located either on the same plant or on different plants. For fertilization to occur, bi-cellular or tri-cellular male gametophytes (pollen grains) have to travel to the immobile female gametophyte in the ovary. To survive exposure to a hostile atmosphere, pollen grains are thought to enter a state of complete or partial developmental arrest (DA). DA in pollen is strongly associated with acquisition of desiccation tolerance (DT) to extend pollen viability during air travel, but occurrence of DA in pollen is both species-dependent and at the same time strongly dependent on the reigning environmental conditions at the time of dispersal. Several environmental stresses (heat, drought, cold, humidity) are known to affect pollen production and viability. Climate change is also posing a serious threat to plant reproductive behavior and crop productivity. It is therefore timely to gain a better understanding of how DA and pollen viability are controlled in plants and how pollen viability can be protected to secure crop yields in a changing environment. Here, we provide an overview of how DA and pollen viability are controlled and how the environment affects them. We make emphasis on what is known and areas where a deeper understanding is needed.